Chemical composition and efficacy of dichloromethane extract of Croton sphaerogynus Baill. (Euphorbiaceae) against the cattle tick Rhipicephalus microplus (Acari: Ixodidae) - Righi, Adne A.; Motta, Lucimar B.; Klafke, Guilherme M.; Pohl, Paula C.; Furlan, Cláudia M.; Santos, Deborah Y.A.C.; Salatino, Maria L.F.; Negri, Giuseppina; Labruna, Marcelo B.; Salatino, Antonio (Elsevier, 2013)
The cattle tick Rhipicephalus microplus is widely distributed in tropical and subtropical regions, causing high economic impact on cattle production. The control of tick infestations is regarded worldwide as critical and has been based on the use of organophosphates, synthetic pyretroids, amitraz and recently ivermectin and fipronil. The present study reports the analysis by gas chromatography/mass spectrometry of the constituents of leaf extracts of Croton sphaerogynus and results of acaricidal activity against the cattle tick R. microplus. The larval package test using the serial dilutions 0.625%, 1.25%, 2.5%, 5.0%, 10.0% and 20.0% (v/v) gave mortality rates 2.25%, 8.26%, 8.81%, 24.80%, 83.66% and 99.32%, respectively. Relevant constituents identified were abietanes, podocarpenes and clerodane type furano diterpenes. The present work may represent a possibility of attainment of natural substances useful for the control of R. microplus. © 2012 Elsevier B.V.
Keywords: Abietane; Acaricidal activity; Euphorbiaceae; Medicinal plants; Rhipicephalus microplus